Social capital and resilience among people living on antiretroviral therapy in resource poor Uganda - Kalule Nanfuka, Esther; Kyaddondo, David; Ssali, Sarah N.; Asingwire, Narathius (PLoS ONE, 2018)
Despite the national roll-out of free HIV medicines in Uganda and other sub-Saharan African countries, many HIV positive patients on antiretroviral therapy (ART) are at risk of no adherence due to poverty and other structural and health system related constraints. However, several patients exhibit resilience by attaining and sustaining high levels of adherence amid adversity. Social capital, defined as resources embedded within social networks, is key in facilitating resilience but the mechanism through which it operates remains understudied. This article provides insights into mechanisms through which social capital enables patients on ART in a resource-poor setting to overcome risk and sustain adherence to treatment.
Keywords: Social capital; Antiretroviral therapy; Resource; Uganda